English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

6 answers

the three consecutive integers would be
x - 1, x, and x + 1

(x - 1) + x + (x + 1) simplifies to 3x.

3x is 3 times the middle number (which is x in our case).

So, yes, it's true.

2007-03-30 08:26:29 · answer #1 · answered by Mathematica 7 · 2 0

Let the numbers be x , (x + 1) and (x + 2)
Sum = x + x + 1 + x + 2
Sum = 3x + 3
Sum = 3.(x + 1)
Sum = 3 times the middle term

2007-03-30 15:31:11 · answer #2 · answered by Como 7 · 0 0

x + (x + 1) + (x + 2) = 3(x + 1)
x + x + 1 + x + 2 = 3(x + 1)
3x + 3 = 3(x + 1)
3(x + 1) = 3(x + 1)

Your Correct.

2007-03-30 15:40:09 · answer #3 · answered by Sherman81 6 · 0 0

Yes, (n-1)+(n)+(n+1)=3n
where n is the middle number

2007-03-30 15:29:04 · answer #4 · answered by w1ckeds1ck312121 3 · 0 0

This is correct

(n-1)+n+(n+1) = 3n + 1 - 1 = 3n

2007-03-30 15:27:40 · answer #5 · answered by Joe the Engineer 3 · 0 0

Yes. I've tried whole numbers, decimals, fractions, negatives, and have included zero. All work out!

2007-03-30 15:31:10 · answer #6 · answered by hrhbg 3 · 0 0

fedest.com, questions and answers